Curriculum Differentiation’s Capacity to Extend Gifted Students in Secondary Mixed-ability Science Classes - Christine Ireland (Turkish Journal of Giftedness and Education, 2020)
Investigated were differences between teachers’ and students’ perceptions of curriculum differentiation strategies to extend highly able students in mixedability secondary science classes. Gifted underachievement and disengagement is increasing in Australian schools, potentially linked to these perception differences regarding curriculum differentiation. 161, Year 7 students, aged aproximately 11 years (n = 29 highly able; n = 132 non-highly able), and 43 science-trained teachers were surveyed. Examined were students’ and teachers’ perceptions of the importance and achievability of 24 curriculum differentiation strategies, within the curriculum components of content, process, product, and environment. Significant dissimilarities occurred regarding curriculum differentiation strategies having been achieved at least once during every work unit. In particular, some strategies requiring modification of the learning environment were considered by highly able students to be significantly less frequently achieved, compared to teachers’ perceptions. Implications for policy and practice were explored. Further research of curriculum differentiation that includes students’ perspectives is required.